2018
DOI: 10.1039/c7cp08166a
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous hydrogen in polymerising plasmas

Abstract: Historically, there have been two opposing views regarding deposition mechanisms in plasma polymerisation, radical growth and direct ion deposition, with neither being able to fully explain the chemistry of the resultant coating. Deposition rate and film chemistry are dependent on the chemistry of the plasma phase and thus the activation mechanisms of species in the plasma are critical to understanding the relative contributions of various chemical and physical routes to plasma polymer formation. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…The sticking probability of ions depends on the ion energy and chemistry, but it is often in the range of 20%–50%. [ 24 ] Our data suggest a significantly lower sticking probability; however, at present, quantitative estimation seems premature. Pending further work, we can conclude that there is a considerable flux of ions (as well as of radicals) and it appears reasonable to postulate that they play a major role in film formation and incorporation of functional groups.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The sticking probability of ions depends on the ion energy and chemistry, but it is often in the range of 20%–50%. [ 24 ] Our data suggest a significantly lower sticking probability; however, at present, quantitative estimation seems premature. Pending further work, we can conclude that there is a considerable flux of ions (as well as of radicals) and it appears reasonable to postulate that they play a major role in film formation and incorporation of functional groups.…”
Section: Resultsmentioning
confidence: 61%
“…Regardless of how the ions are produced, though, the mass spectrometer measures the ionic species that reach surfaces in contact with the plasma, thus contributing to film deposition. The efficient generation of (M + H) + is probably due to two factors: first, the high abundance and promiscuity of H + in plasmas [ 24 ] and, second, resonance stabilization of the charge that arises upon addition of a proton to ester and carboxylic acid groups.…”
Section: Resultsmentioning
confidence: 99%
“…This is further favored by the greater mobility of light CHx• compared with heavier C2Hy• species, which results in more collisions in the discharge zone, hence more recombination reactions. 62 The outcome is dominating recombination to form C2H6, 5,63 which in turn reduces molecular density in the discharge zone and leads to miscalculation of Em per CH4 molecule. Substantial recombination of CH3• to form C2H6 was also reported by modelling of DBD assisted dry reforming of methane (CHEMKIN-PRO software).…”
Section: Methanementioning
confidence: 99%
“…While this approach has been useful in improving structural retention of the precursor, the deposition rate is reduced and the lower energy density can lead to unstable films. Additionally, particularly for saturated hydrocarbons, it has been shown that protonated precursor ions with moderate ion energies are effective at retaining structural motifs 22 . During the on-phase, and extending into the off-phase of pulsed plasmas, the ion energies can be quite high and thus this work will be relevant to both continuous and pulsed plasma regimes.…”
Section: The Ion Energy Distributions Shown Inmentioning
confidence: 99%
“…For very low pressures, this is certainly the case as ions created in the bulk of the plasma gain kinetic energy while passing corresponding to H3O + which is ubiquitous and crucial for protonation in hydrocarbon plasmas. 18 Ions larger than the precursor molecule were also observed, with the second most intense peak assigned to the protonated dimer (2M+H) + at 177 m/z. Proposed structures for these peaks are shown in Scheme 1.…”
mentioning
confidence: 99%